FUNGSI YAMA KOTOBA DALAM NOVEL KAIKO NO MORI - Ni Putu Luhur Wedayanti (Program Magister Linguistik Universitas Udayana, 2014)
Yama kotoba as a language which is the identity of the Matagi has the function of language as language functions presented by Halliday and Hasan (1985:17). Yama kotoba has three main functions of language that is informative functions that provide information about things that matagi belief, weather and natural conditions where the Matagi hunting and hunting system that is used by Matagi along with the hunting group. Interactive functions of yama kotoba are about taboo things that should not be done at all because it can lead to bad things against Matagi themselves and the group. Interactive functions in social control also refers to the interactive functions to support the environment, as yama kotoba delivered on the function of social control or command lists to ban some things taboo. The taboo things that can help Matagi maintain balance and preservation of nature in the mountains. Then, yama kotoba’s Imaginative Function consist of ritual and poetic function.